The challenges of urban sprawl and its impacts on the fragmented agricultural lands: A case study of Tersa, Giza - Youssef, Aya Farid (AUC Knowledge Fountain, 2019)
Parallel to the fast growing population, the whole world in general and the developing countries in particular are experiencing an unusual rapid rate of urbanization. Unmanaged urban sprawl is one of the major challenges in the urbanization process. Urban sprawl occurs as an expansion over the limited fertile land and therefore adds more stress to agricultural resources, food security as well as stressing the available infrastructure. This research aims to study and highlight the influences of urban sprawl on the agricultural lands in Egypt with particular emphasis on the fragmented agricultural lands produced by it. The study sheds light on a case study in Giza governorate (Tersa district). The research affirms that urban sprawl has direct and indirect impacts on the various dimensions of the agricultural process in Tersa and in turn influences crop production and food security. Urban sprawl led to losing about 19 percent of Tersa’s fertile agricultural lands between 2007 and 2017. Farmers of the remaining agricultural lands face many challenges in traditional farming practices. Crop type has totally changed as a result of polluted irrigation water and other practices of the surrounding urban residents. Accordingly, the remaining agricultural lands are losing its soil fertility. The study is investigating the impact of the urban sprawl in Tersa district on agricultural resources over a ten years period between 2007 and 2017. It attempts to answer the research questions through integrating remote sensing data and primary data obtained from conducted social study in four areas within Tersa. In addition, irrigation water samples were collected and analyzed to evaluate irrigation water quality which is considered a major dimension influencing the changes of crop production.